Stocking densities of juvenile Brycon orthotaenia: production parameters and economic benefits in net cages - Aline de Assis Lago; Rilke Tadeu Fonseca de Freitas; Maria Emília de Sousa Gomes Pimenta; Bruno Olivetti de Mattos; Rafael Vilhena Reis Neto; Adriano Carvalho Costa (Acta Scientiarum. Animal Sciences, 2014)
Developing a rearing technology requires the determination of the optimum stocking density. This study aimed to determine the best stocking density for Brycon orthotaenia juveniles grown in net cages, during the rearing phase. The research was conducted at the Experimental Farm of EPAMIG, in Felixlândia, Minas Gerais State, in the Três Marias Reservoir. 9,000 fingerlings were distributed into 12 net cages, 2 m3each, according to a completely randomized design with three replications and four different stocking densities (150, 300, 450, 600 fish m-3). Random samples were taken from each net cage, at the onset of the experiment and at 60 rearing days, to assess production parameters, specific growth rate and uniformity. We verified a positive linear relationship (p < 0.05) for final biomass (r2 = 0.88), weight gain (r2 = 0.87), productivity (r2 = 0.86), apparent feed conversion (r2 = 0.96) and economic viability (r2 = 0.96). For survival (r2 = 0.98), the relationship was negative (p < 0.05). There were no significant differences between treatments (p > 0.05) for growth parameters, uniformity and final weight. It can be concluded that the density of 300 fish m-3 is the most suitable, because it provides higher net revenue, survival, and a good feed conversion.